2017
DOI: 10.1007/s00508-017-1222-y
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic factors associated with the 1‑year prevalence of severe pain and pain-related sickness absence in the Austrian population

Abstract: SummaryBackgroundThe aim of this study was to (1) investigate the relation of socio-economic status (SES), measured as education, occupation, and income, with the 12-month prevalence of severe pain and with pain-related sickness absence, and (2) analyse to what extent sociodemographic and medical factors influence these associations.MethodsThe study population comprised 8084 subjects aged between 15 and 65 years from the Austrian Health Interview Survey in 2006/07. Associations of SES with the 1‑year prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…A questionnaire was specifically designed for this study. Because previous population-based studies have reported a significant associations between socio-demographic factors, particularly low socio-economic status (as measured by education and income), and pain [ 31 33 ], socio-demographic variables in the questionnaire included gender, age, education years, marital status, employment status, and self-rated financial status (good, fair, poor). Because substance use characteristics (i.e., long-term heroin use and injection drug use) and psychological factors have been found to be significantly associated with pain [ 34 36 ], clinical data collected in the study were usual route of past heroin administration (smoking, injecting), duration of past heroin use, duration of MMT, methadone dosage, depression, and anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…A questionnaire was specifically designed for this study. Because previous population-based studies have reported a significant associations between socio-demographic factors, particularly low socio-economic status (as measured by education and income), and pain [ 31 33 ], socio-demographic variables in the questionnaire included gender, age, education years, marital status, employment status, and self-rated financial status (good, fair, poor). Because substance use characteristics (i.e., long-term heroin use and injection drug use) and psychological factors have been found to be significantly associated with pain [ 34 36 ], clinical data collected in the study were usual route of past heroin administration (smoking, injecting), duration of past heroin use, duration of MMT, methadone dosage, depression, and anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…In Austria 25% of the adult population is affected by chronic pain [ 2 ]. These prevalence rates vary by the types of conditions of chronic pain and rates are higher for women and older adults or subjects with lower educational level [ 3 5 ]. Sociodemographic factors, such as sex interact with the mechanisms of coping with chronic pain [ 2 , 6 , 7 ] and therefore play an important role in the consequences of chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…In this edition, one article shows that 32.9% of the employed Austrian population aged 15-65 years who are affected by severe pain, were on sick leave due to pain. Education, income, and type of employment were significantly associated with absenteeism due to pain, at given pain intensity, comorbidities and sociodemographic factors [9]; however, many people stay at the workplace despite chronic pain, with their working ability being affected. Furthermore, estimates show that this presenteeism due to chronic pain, leads to four times more hours of work disability than absenteeism due to chronic pain [10].…”
Section: Implication Of Pain On Societymentioning
confidence: 99%